The interaction between monetary and macroprudential policy: Should central banks 'lean against the wind' to foster macro-financial stability? - Sebastian Krug (Economics: The Open-Access, Open-Assessment E-Journal, 2018)
The extensive harm caused by the financial crisis raises the question of whether policy- makers could have done more to prevent the build-up of financial imbalances. This paper aims to contribute to the field of regulatory impact assessment by taking up the revived debate on whether central banks should use the interest rate to directly respond to the build-up of financial sector imbalances, i.e. 'lean against the wind' or not. Currently, there is no consensus on whether monetary policy is, in general, able to support the resilience of the financial system or if this task should better be left to the macroprudential approach of financial regulation. The author aims to shed light on this issue by analyzing distinct policy regimes within an agent-based computational macro-model with endogenous money. He finds that policies that make use of their comparative advantage lead to superior outcomes concerning their respective intended objectives. In particular, he shows that 'leaning against the wind' should only serve as first line of defense in the absence of a prudential regulatory regime and that price stability does not necessarily mean financial stability. Moreover, macroprudential regulation as unburdened policy instrument is able to dampen the build-up of financial imbalances by restricting credit to the unsustainable high-leveraged part of the real economy.
Keywords: E44; E50; G01; G28; C63; 330; financial stability; monetary economics; macroprudential policy; financial regulation; central banking; agent-based macroeconomics